(3HQeLI bhGYO GdHjGfGJ HGSJNOGe (B\cs - (3YeG ehSi(B.s; (3YeGQ ehSi(B.s ((3MdH (B:s (3TYGY ddfTQ h GdYdhe(B,s, 2004)
(3jJfGhd cjajI GSJNOGe HjFI (Bnet., (3h dZI (Bc\ (3ef GLd JWHjbGJ (Bwindows (3h (Basp.net (3JYJeO bhGYO GdHjGfGJ(B.s
(3bhGYO GdHjGfGJ (B.s
Keywords: (3bhGYO HjGfGJ (B- (3HQeLI(B.s